ANALISIS KUALITAS PELAYANAN SUB BAGIAN AKADEMIK (SBA PROGRAM VOKASI UNIVERSITAS INDONESIA - Sancoko, Sancoko; Riduansyah, Mohammad; Nofiantoro, Wahyu (Jurnal Vokasi Indonesia, 2016)
Measurement tools service quality is using Serv Quality Method. In this study, we tried to see different gap between students' perceptions of employee performance with the level of interest/expectations of students to an existing service using five indicators Serv Quality. Aspects studied is, reliability aspects, responsiveness aspect, assurance Aspects, empathy aspects, and the tangibles aspects. SBA research object because they become the frontline in shaping the image of the ministry in Program vocational UI. The method used in this research is descriptive analysis method with quantitative approach., ie research that describes a data collection on the observations that have been made. This research activity is a continuation of research since the first semester of 2014/2015 to the first semester of 2015/2016. The population in this study is that students of Administration UI vocational program. Based on the results of this study concluded that there is still a big gap to the five dimensions of Quality Serv.